TRP Channels in Tumoral Processes Mediated by Oxidative Stress and Inflammation - Florentina Piciu; Mihaela Balas; Madalina Andreea Badea; Dana Cucu (MDPI AG, 2023)
The channels from the superfamily of transient receptor potential (TRP) activated by reactive oxygen species (ROS) can be defined as redox channels. Those with the best exposure of the cysteine residues and, hence, the most sensitive to oxidative stress are TRPC4, TRPC5, TRPV1, TRPV4, and TRPA1, while others, such as TRPC3, TRPM2, and TRPM7, are indirectly activated by ROS. Furthermore, activation by ROS has different effects on the tumorigenic process: some TRP channels may, upon activation, stimulate proliferation, apoptosis, or migration of cancer cells, while others inhibit these processes, depending on the cancer type, tumoral microenvironment, and, finally, on the methods used for evaluation. Therefore, using these polymodal proteins as therapeutic targets is still an unmet need, despite their draggability and modulation by simple and mostly unharmful compounds. This review intended to create some cellular models of the interaction between oxidative stress, TRP channels, and inflammation. Although somewhat crosstalk between the three actors was rather theoretical, we intended to gather the recently published data and proposed pathways of cancer inhibition using modulators of TRP proteins, hoping that the experimental data corroborated clinical information may finally bring the results from the bench to the bedside.